Sense-B-noise: an enigmatic cause for inappropriate shocks in subcutaneous implantable cardioverter defibrillators. Issue 2 (10th November 2022) - Haeberlin, Andreas; Burri, Haran; Schaer, Beat; Koepfli, Pascal; Grebmer, Christian; Breitenstein, Alexander; Reichlin, Tobias; Noti, Fabian
Abstract: Aims: Subcutaneous implantable cardioverter defibrillators (S-ICDs) are well established. However, inappropriate shocks (IAS) remain a source of concern since S-ICDs offer very limited troubleshooting options. In our multicentre case series, we describe several patients who experienced IAS due to a previously unknown S-ICD system issue. Methods and results: We observed six patients suffering from this novel IAS entity. The IAS occurred exclusively in primary or alternate S-ICD sensing vector configuration (therefore called 'Sense-B-noise'). IAS were caused by non-physiologic oversensing episodes characterized by intermittent signal saturation, diminished QRS amplitudes, and disappearance of the artefacts after the IAS. Noise/oversensing could not be provoked by manipulation, X-ray did not show evidence for lead/header issues and impedance measurements were within normal limits. The pooled experience of our centres implies that up to ∼5% of S-ICDs may be affected. The underlying root cause was discussed extensively with the manufacturer but remains unknown and is under further investigation. Conclusion: Sense-B-noise is a novel cause for IAS due to non-physiologic signal oversensing, arising from a previously unknown S-ICD system issue. Sense-B-noise may be suspected if episodes of signal saturation in primary or alternate vector configuration are present, oversensing cannot be provoked, and X-ray and electrical measurements appear normal. The issue can be resolved by reprogramming the device to secondary sensing vector.